Effect of Posterior Subtenon Triamcinolone Acetonide in Refractory Diabetic Macular Edema - Habib, Muhammad Kashif; Shafqat, Rubab; Oozeerkhan, Zeeshan Khan; Gul, Anwar Ahmed; Jabeen, Nighat; Sadiq, Muhammad Usman (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To see the effect of Posterior Subtenon Triamcinolone Acetonide (PSTT) injection in refractory Diabetic Macular Edema (DME).Study Design: Quasi-Experimental Study.Place and Duration of Study: Retina Clinic, Al-Shifa Trust Eye Hospital, Rawalpindi, from Jun to Dec 2018.Methodology: Patients with Clinically Significant Macular Edema (CSME), with Central Macular Thickness (CMT) >300 microns and those who did not respond to three consecutive Intra-Vitreal Bevacizumab (IVB) injections were included. Posterior Subtenon Triamcinolone Acetonide (PSTT) was administered by a single retina fellow using the same protocol. Each patient’s best-corrected visual acuity (BCVA), Intra-ocular pressure (IOP) and Central Macular Thickness (CMT) were evaluated on the day of Posterior Subtenon Triamcinolone Acetonide (PSTT) injection and again at 1, 3 and 6 months.Results: Out of 52 patients (104 eyes), 16 females and 36 males were present. The mean age was 57.67±9.35 years. Out of 52 right eyes, the mean Central Macular Thickness (CMT) at the first visit was 388.83±172.04 µm, 332.81 ± 144.69 µm after one month, 292.81±147.59µm after six months of Posterior Subtenon Triamcinolone Acetonide (PSTT) Injection. Similarly, for 52 left eyes mean Central Macular Thickness (CMT) at the first visit is 375.79±160.81 µm, 364.52 ± 167.95 µm after one month and 323.37±155.74 µm after six months. Similar results were observed for IOP and BCVA.Conclusion: Posterior Subtenon Triamcinolone (PSTT) injections are effective in diabetic macular oedema, which does not respond to intravitreal anti-VEGF (IVB) therapy.